Progress unveiled: a comprehensive review on non-toxic carbon-based quantum dots - synthesis, unique properties, and diverse applications - Mathad, Shridhar N.; Sangam, Sheela; Bakale, Raghavendra; Shirgaonkar, Deepak B. (Physics and Chemistry of Solid State, 2024)
Carbon-based quantum dots (CQDs) represent a highly promising category of nanomaterials due to their distinctive optical, electronic, and chemical characteristics. This review delves into the synthesis methodologies of non-toxic CQDs, with particular emphasis on eco-friendly approaches that minimize environmental impact. The discussion spans their diverse applications across various domains, highlighting their role in pushing the boundaries of sustainability. Notably, the review elucidates the optical attributes of non-toxic CQDs, underscoring their tunable fluorescence, a feature that renders them invaluable for applications in bioimaging, sensors, and optoelectronic devices. Moreover, their non-toxic nature is pivotal for biomedical endeavors, facilitating advancements in drug delivery, photothermal therapy, and bio-labeling. In addition to their biomedical potential, this review delves into the utility of non-toxic CQDs in environmental sensing and catalysis, showcasing their adaptability and multifunctionality. Through an in-depth exploration of recent advancements, challenges, and future prospects, this comprehensive review aims to provide invaluable insights into the burgeoning field of non-toxic CQD research, propelling the development of sustainable and innovative technologies.